Bruce Mannheim, The Language of the lnka since the European lnvasion - Sánchez Arroba, María Elena (Pontificia Universidad Católica del Perú. Fondo Editorial, 1995)
BRUCE, MANNHEIM. The Language of the lnka since the European lnvasion, Austin, University of Texas Press, 1991, 326 p.
Keywords: Lingüística; Reseñas Bibliográficas; https://purl.org/pe-repo/ocde/ford#6.02.06